Anisotropic cosmological models of Bianchi types III and V in Lyra's geometry - Ram S.; Singh P. (My University, 2025)
Exact solutions to Einstein's equations are presented in vacuum and in the presence of stiff matter for spatially homogeneous cosmological models of Bianchi types type III and V in the normal gauge for Lyra's geometry. Solutions represent anisotropic cosmological universes which contract from infinite volume at the initial time singularity T=0 to zero volume as T→∞. Some physical properties of the models are also discussed. © 1992 Plenum Publishing Corporation.